2014
DOI: 10.1128/mcb.00295-14
|View full text |Cite
|
Sign up to set email alerts
|

STAT1β Is Not Dominant Negative and Is Capable of Contributing to Gamma Interferon-Dependent Innate Immunity

Abstract: The transcription factor STAT1 is essential for interferon (IFN)-mediated immunity in humans and mice. STAT1 function is tightly regulated, and both loss-and gain-of-function mutations result in severe immune diseases. The two alternatively spliced isoforms, STAT1␣ and STAT1␤, differ with regard to a C-terminal transactivation domain, which is absent in STAT1␤. STAT1␤ is considered to be transcriptionally inactive and to be a competitive inhibitor of STAT1␣. To investigate the functions of the STAT1 isoforms i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
53
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 72 publications
(82 reference statements)
2
53
2
Order By: Relevance
“…BMDMs from STAT1 ␤/␤ mice exhibit reduced induction of GAS-driven genes in response to IFN-␥, but not all target genes are affected to the same extent (15). The expression of ISRE-driven genes is not grossly affected in STAT1 ␤/␤ BMDMs stimulated by IFN-␤, indicating that the ISGF3 complex is fully functional in these cells.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…BMDMs from STAT1 ␤/␤ mice exhibit reduced induction of GAS-driven genes in response to IFN-␥, but not all target genes are affected to the same extent (15). The expression of ISRE-driven genes is not grossly affected in STAT1 ␤/␤ BMDMs stimulated by IFN-␤, indicating that the ISGF3 complex is fully functional in these cells.…”
Section: Resultsmentioning
confidence: 74%
“…The expression of ISRE-driven genes is not grossly affected in STAT1 ␤/␤ BMDMs stimulated by IFN-␤, indicating that the ISGF3 complex is fully functional in these cells. The Irf1 and Socs1 genes were shown to be significantly less induced in IFN-␥-stimulated STAT1 ␤/␤ BMDMs than in IFN-␥-stimulated WT BMDMs (15). IFN-␤ treatment of STAT1 ␤/␤ BMDMs and analysis of pre-mRNA expression of Irf1 and Socs1 demonstrated that STAT1␤ homodimers were less transcriptionally active at these genes in type I IFN responses also ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A20 markedly suppressed the basal STAT1 protein levels (figure 3A, B). There are two alternatively spliced isoforms of STAT1 that can both participate in STAT1-dependent immunity: STAT1α and STAT1β 15. Both STAT1α and STAT1β protein levels were suppressed by A20, but the effect was more pronounced for STAT1β, leading to a lower STAT1α/STAT1β ratio in the absence of A20 (figure 3B).…”
Section: Resultsmentioning
confidence: 99%